Physical activity, sedentary behavior and diabetes - Dunstan, David (Henry Stewart Talks, 2013)
Epidemiological thinking: physical activity & health, Skeletal muscle, glucose disposal and muscle glucose uptake, Recent advances in exercise and T2DM, Exercise modality, combination training and rationale for strength, resistance training, Exercise guidelines for T2DM (2006), Change in HbA1c, ‘Stickiness’, Community centre vs. home based resistance training, Physical activity recommendations and public health, The 'sitting orientated’ society, Sedentary behaviours and mortality, Movement and posture measurement devices, Sedentary time and breaks (NHANES), Australian adults’ overall daily behaviour patterns, Rethinking the physical activity paradigm, Pathophysiology of prolonged sitting, Sedentary time and light-intensity activity, How to reduce sitting time and guidance for prescribing exercise and physical activity promotion, ACSM position stand